High-rate silicon-oxygen negative electrode material for lithium battery and preparation method of high-rate silicon-oxygen negative electrode material
By introducing a carbon cladding layer into the SiOx-based negative electrode material, the transmission rate of Li+ ions is improved, the problem of limited charging rate of lithium batteries is solved, and a high-rate silicon oxygen negative electrode material with high magnification and good cycling performance is achieved.
Patent Information
- Application Number
- CN202411559251.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
The Li+ ion transmission rate in SiOx-based anode material is limited, resulting in the charging rate of lithium batteries being limited, which cannot meet the needs of fast charging.
A high-ratio silicon oxygen negative electrode material including a core and a cladding layer is used. The core material is SiOx (x value is 0.8-1.2), and the cladding layer is a carbon cladding layer. The material is prepared by steps such as crushing, alkali etching, water washing, drying and carbon coating.
It improves the transmission rate of Li+ ions, enhances the rate performance of the material, and can significantly improve the rate performance and cycle performance of the material. It is suitable for fast-charging lithium batteries.
Smart Images

Figure CN119419250A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicon oxygen negative electrode materials for lithium batteries, relates to high-rate silicon oxygen negative electrode materials for lithium batteries, and also relates to a preparation method of high-rate silicon oxygen negative electrode materials for lithium batteries. Background Art
[0002] As the demand for high-capacity batteries continues to increase, graphite materials have a relatively low theoretical specific capacity (372 mAh g -1 ) has limited its development. Silicon-based composite materials have received special attention in the next generation of lithium-ion batteries. Their theoretical specific capacity is as high as 4200mAh / g, which is 10 times the capacity of traditional graphite materials and can greatly improve the energy density of lithium batteries. Silicon-oxygen negative electrode materials can better alleviate the volume expansion problem during the charging and discharging process, thereby improving the cycle stability and service life of the battery. In addition, silicon-oxygen negative electrode materials also have good conductivity and thermal stability, which helps to improve the overall performance of the battery.
[0003] However, alloying / de-alloying of Si with Li can lead to drastic volume changes, causing electrode cracking or pulverization, resulting in rapid capacity decay and poor cycling performance. x During the initial lithiation process of the base material, Li and SiO x The Li2O produced by the reaction can serve as a buffer component to improve the cycling performance of the electrode. At the same time, the resulting nano-silicon is evenly distributed in the Li2O matrix, giving the electrode a high specific capacity. x The base material still has the problem of poor conductivity, usually graphite composite SiO x , improve its electronic conductivity and prevent the derived nano-scale Si from agglomerating, synthesized SiO x / C nanocomposites have high specific capacity and good cycle performance. However, due to the popularity of new energy vehicles, people's demand for fast charging is becoming more and more urgent. In order to eliminate the obstacle of "range anxiety", the development of negative electrode materials suitable for high-capacity batteries and fast-charging batteries is an inevitable trend in the development of the lithium battery industry. The realization of extremely fast-charging batteries requires solving many technical problems, among which a key problem is diffusion limitation. Si-based and its SiO x The basic negative electrode materials are facing the dilemma of poor rate performance. The first thing to be solved is the Li + The transport rate of ions is limited, which limits the charging rate of the battery. Summary of the invention
[0004] The purpose of the present invention is to provide a high-rate silicon-oxygen negative electrode material for lithium batteries, which solves the problem of SiO x Li in base negative electrode material + The problem of limited ion transport rate is solved, which improves the rate performance of the material.
[0005] The present invention also aims to provide a method for preparing a high-rate silicon-oxygen negative electrode material for a lithium battery.
[0006] The first technical solution adopted by the present invention is that the high-rate silicon-oxygen negative electrode material for lithium batteries includes a core and a coating layer, wherein the core material is SiO x , where x is 0.8-1.2; the coating layer is a carbon coating layer.
[0007] The second technical solution adopted by the present invention is a method for preparing a high-rate silicon-oxygen negative electrode material for a lithium battery, and the specific operating steps are as follows:
[0008] Step 1: Select silicon oxide raw material SiO x , wherein x is 0.8-1.2; using a crushing device to crush the silicon oxygen raw material SiO x crush;
[0009] Step 2, etching the material crushed in step 1 with an alkaline solution to obtain a surface-modified porous structure material;
[0010] Step 3, washing the material after alkali etching in step 2 with deionized water until the pH value of the solution is neutral, and drying the washed material in an oven;
[0011] Step 4, placing the dried material in a coating device for pyrolysis coating, and obtaining a high-rate silicon-oxygen negative electrode material after cooling.
[0012] The second technical solution of the present invention is also characterized in that:
[0013] Furthermore, the pulverizing equipment in step 1 includes one or more of a toothed pulverizer, a hammer pulverizer, a knife pulverizer, a turbine pulverizer, a pressure mill pulverizer, a milling pulverizer, a jet pulverizer, a ball mill or a sand mill.
[0014] Furthermore, in step 1, the silicon-oxygen raw material SiO x After crushing, 50% of the particles have a size of 4-7um.
[0015] Furthermore, the alkaline solution in step 2 is one or more of NaOH solution and KOH solution.
[0016] Furthermore, the concentration of the alkaline solution in step 2 is 0.5-1.5 mol / L, and the reaction time is 5-7h.
[0017] Furthermore, the water washing in step 3 is to wash the alkali-etched material in step 2 with deionized water until it is neutral, and the water washing equipment is one or more of a centrifuge and a positive pressure filtration equipment; the selected oven drying temperature is 70-90°C, and the drying time is 12-18h.
[0018] Further, step 4 is as follows: add the dried material in step 3 into a rotary kiln, the reaction temperature is 800-950°C, acetylene is introduced at a flow rate of 0.6-1.0L / min for carbon coating, the reaction is carried out for 2-5h, and after cooling, a high-rate silicon-oxygen negative electrode material is obtained.
[0019] Furthermore, in step 4, the carbon coating method may also be asphalt pyrolysis coating.
[0020] The beneficial effects of the present invention are:
[0021] (I) The preparation of the high-rate silicon-oxygen material of the present invention is obtained by modifying powdered conventional silicon-oxygen. It mainly involves mechanically crushing block silicon-oxygen particles to obtain granular powdered silicon-oxygen, and then performing alkaline etching, washing, drying, and crushing processes on the crushed granular silicon-oxygen to modify the surface, and then performing a carbon coating process to obtain a high-rate silicon-oxygen material. The selected powdered silicon-oxygen raw material is a mainstream product in the market, which is conducive to industrial preparation, and the selection of a single batch of raw materials solves the stability problem of material preparation.
[0022] (II) The present invention modifies the material by alkaline etching and surface coating, and then develops a high-rate silicon-oxygen negative electrode material. This is mainly aimed at the problem of poor conductivity and poor rate performance of silicon-oxygen negative electrode materials. The alkaline is used to in-situ etch silicon-oxygen to increase the porosity, increase the contact between the sample and the electrolyte, shorten the lithium ion transmission path, and improve the Li + The diffusion coefficient can greatly improve the rate performance. Carbon coating adopts the vapor deposition process to improve its conductivity, which can significantly improve the rate performance and cycle performance of the material. Silicon-oxygen negative electrode can be better used in the field of energy storage and power batteries in the layout of new energy industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a flow chart of the preparation method of the high-rate silicon-oxygen negative electrode material of the present invention.
[0024] Figure 2 This is a SEM image of the high-rate silicon-oxygen negative electrode material prepared in Example 1 of the present invention.
[0025] Figure 3 This is the XRD spectrum of the high-rate silicon-oxygen negative electrode material prepared in Example 1 of the present invention.
[0026] Figure 4 This is the charge and discharge curve of the high-rate silicon-oxygen negative electrode material prepared in Example 1 of the present invention.
[0027] Figure 5 This is a rate performance diagram of the high-rate silicon-oxygen negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The high-rate silicon-oxygen negative electrode material for lithium batteries of the present invention comprises a core and a coating layer, wherein the core material is SiO x , where x is 0.8-1.2; the coating layer is a carbon coating layer.
[0029] The preparation method of the high-rate silicon-oxygen negative electrode material for lithium battery of the present invention is as follows: Figure 1 The specific steps are as follows:
[0030] Step 1: Select silicon oxide raw material SiO x , wherein x is 0.8-1.2; using a crushing device to crush the silicon oxygen raw material SiO x Crushing; Silicon oxide raw materials SiO x After crushing, 50% of the particles have a particle size of 4-7um;
[0031] The crushing equipment includes one or more of a tooth crusher, a hammer crusher, a knife crusher, a turbine crusher, a pressure mill crusher, a milling crusher, a jet crusher, a ball mill or a sand mill.
[0032] Step 2, etching the material crushed in step 1 with an alkaline solution to obtain a surface-modified porous structure material; the alkaline solution is one or more of a NaOH solution and a KOH solution; the concentration of the alkaline solution is 0.5-1.5 mol / L, and the reaction time is 5-7h;
[0033] Step 3, washing the material after alkaline etching in step 2 with deionized water, the washing equipment is one or more of a centrifuge and a positive pressure filtration equipment; washing until the pH value of the solution is neutral, and drying the washed material in an oven; the oven drying temperature is 70-90°C, and the drying time is 12-18h.
[0034] Step 4, placing the dried material in a coating device for pyrolysis coating, and obtaining a high-rate silicon-oxygen negative electrode material after cooling.
[0035] The dried material in step 3 is added into a rotary kiln, the reaction temperature is 800-950°C, acetylene is introduced at a flow rate of 0.6-1.0 L / min for carbon coating, the reaction is carried out for 2-5 hours, and a high-rate silicon-oxygen negative electrode material is obtained after cooling.
[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0037] Example 1
[0038] The preparation method of the high-rate silicon-oxygen negative electrode material for lithium batteries of the present invention has the following specific operating steps:
[0039] Step 1, precursor preparation: select conventional SiO x (x≈1.02) is used as the raw material and further crushed by a jet mill. The parameters are adjusted to ensure that the material D50 is 6-7um, which is recorded as precursor A.
[0040] Step 2, alkaline solution etching: weigh an appropriate amount of NaOH to prepare a 1 mol / L (abbreviated as M under mol / L) NaOH solution, and then weigh the precursor A obtained in step 1 at a ratio of 1 kg precursor A: 2.5 L NaOH solution for alkaline etching, mechanically stir for 6 hours, wash with deionized water to neutrality, dry at 80°C for 12 hours and set aside, recorded as precursor B.
[0041] Step 3, carbon coating: 1 kg of precursor B was put into a rotary kiln for gas phase carbon coating, with an acetylene flow rate of 0.8 L / min, and the temperature was increased to 900°C at a heating rate of 5°C / min and kept at this temperature for 3 hours. After naturally cooling to room temperature, a carbon-based negative electrode material for lithium storage was obtained.
[0042] Step 4, testing the physicochemical parameters of the material obtained in step 3, assembling it into a lithium-ion battery, and testing the relevant electrochemical properties.
[0043] Example 2
[0044] The preparation method of the high-rate silicon-oxygen negative electrode material for lithium batteries of the present invention has the following specific operating steps:
[0045] Step 1, precursor preparation: select conventional SiO x (x≈1.02) is used as the raw material and further crushed by a jet mill. The parameters are adjusted to ensure that the material D50 is 6-7um, which is recorded as precursor A.
[0046] Step 2, alkaline solution etching: weigh an appropriate amount of NaOH to prepare a 0.5 mol / L (abbreviated as M under mol / L) NaOH solution, and then weigh the precursor A obtained in step 1 at a ratio of 1 kg precursor A: 2.5 L NaOH solution for alkaline etching, mechanically stir for 6 hours, wash with deionized water to neutrality, dry at 80°C for 12 hours and set aside, recorded as precursor B.
[0047] Step 3, carbon coating: 1 kg of precursor B was put into a rotary kiln for gas phase carbon coating, with an acetylene flow rate of 0.8 L / min, and the temperature was increased to 900°C at a heating rate of 5°C / min and kept at this temperature for 3 hours. After naturally cooling to room temperature, a carbon-based negative electrode material for lithium storage was obtained.
[0048] Step 4, testing the physicochemical parameters of the material obtained in step 3, assembling it into a lithium-ion battery, and testing the relevant electrochemical properties.
[0049] Example 3
[0050] The preparation method of the high-rate silicon-oxygen negative electrode material for lithium batteries of the present invention has the following specific operating steps:
[0051] Step 1, precursor preparation: select conventional SiO x (x≈1.02) is used as the raw material and further crushed by a jet mill. The parameters are adjusted to ensure that the material D50 is 6-7um, which is recorded as precursor A.
[0052] Step 2, alkaline solution etching: weigh an appropriate amount of NaOH to prepare a 1.5 mol / L (abbreviated as M under mol / L) NaOH solution, and then weigh the precursor A obtained in step 1 at a ratio of 1 kg precursor A: 2.5 L NaOH solution for alkaline etching, mechanically stir for 6 hours, wash with deionized water to neutrality, dry at 80°C for 12 hours and set aside, recorded as precursor B.
[0053] Step 3, carbon coating: 1 kg of precursor B was put into a rotary kiln for gas phase carbon coating, with an acetylene flow rate of 0.8 L / min, and the temperature was increased to 900°C at a heating rate of 5°C / min and kept at this temperature for 3 hours. After naturally cooling to room temperature, a carbon-based negative electrode material for lithium storage was obtained.
[0054] Step 4, testing the physicochemical parameters of the material obtained in step 3, assembling it into a lithium-ion battery, and testing the relevant electrochemical properties.
[0055] Example 4
[0056] The preparation method of the high-rate silicon-oxygen negative electrode material for lithium batteries of the present invention has the following specific operating steps:
[0057] Step 1, precursor preparation: select conventional SiO x (x≈1.02) is used as the raw material and further crushed by a jet mill. The parameters are adjusted to ensure that the material D50 is 6-7um, which is recorded as precursor A.
[0058] Step 2, alkaline solution etching: weigh an appropriate amount of NaOH to prepare a 1 mol / L (abbreviated as M under mol / L) NaOH solution, and then weigh the precursor A obtained in step 1 at a ratio of 1 kg precursor A: 2.5 L NaOH solution for alkaline etching, mechanically stir for 6 hours, wash with deionized water to neutrality, dry at 80°C for 12 hours and set aside, recorded as precursor B.
[0059] Step 3, carbon coating: 1 kg of precursor B was put into a rotary kiln for gas phase carbon coating, with an acetylene flow rate of 0.8 L / min, and the temperature was increased to 820°C at a heating rate of 5°C / min and kept for 3 hours. After naturally cooling to room temperature, a carbon-based negative electrode material for lithium storage was obtained.
[0060] Step 4, testing the physicochemical parameters of the material obtained in step 3, assembling it into a lithium-ion battery, and testing the relevant electrochemical properties.
[0061] Example 5
[0062] The preparation method of the high-rate silicon-oxygen negative electrode material for lithium batteries of the present invention has the following specific operating steps:
[0063] Step 1, precursor preparation: select conventional SiO x (x≈1.02) is used as the raw material and further crushed by a jet mill. The parameters are adjusted to ensure that the material D50 is 6-7um, which is recorded as precursor A.
[0064] Step 2, alkaline solution etching: weigh an appropriate amount of NaOH to prepare a 1 mol / L (abbreviated as M under mol / L) NaOH solution, and then weigh the precursor A obtained in step 1 at a ratio of 1 kg precursor A: 2.5 L NaOH solution for alkaline etching, mechanically stir for 6 hours, wash with deionized water to neutrality, dry at 80°C for 12 hours and set aside, recorded as precursor B.
[0065] Step 3, carbon coating: 1 kg of precursor B was put into a rotary kiln for gas phase carbon coating, with an acetylene flow rate of 0.8 L / min, and the temperature was increased to 945°C at a heating rate of 5°C / min and kept for 3 hours. After naturally cooling to room temperature, a carbon-based negative electrode material for lithium storage was obtained.
[0066] Step 4, testing the physicochemical parameters of the material obtained in step 3, assembling it into a lithium-ion battery, and testing the relevant electrochemical properties.
[0067] Example 6
[0068] The preparation method of the high-rate silicon-oxygen negative electrode material for lithium batteries of the present invention has the following specific operating steps:
[0069] Step 1, precursor preparation: select conventional SiO x (x≈1.02) is used as the raw material and further crushed by a jet mill. The parameters are adjusted to ensure that the material D50 is 6-7um, which is recorded as precursor A.
[0070] Step 2, alkaline solution etching: weigh an appropriate amount of NaOH to prepare 0.5 mol / L (abbreviated as M under mol / L) NaOH solution, and then weigh the precursor A obtained in step 1 at a ratio of 1 kg precursor A: 2.5 L NaOH solution for alkaline etching, mechanically stir for 6 hours, wash with deionized water to neutrality, dry at 80°C for 12 hours and set aside, recorded as precursor B.
[0071] Step 3, carbon coating: 1 kg of precursor B was put into a rotary kiln for gas phase carbon coating, acetylene flow rate was 0.8 L / min, the temperature was increased to 865°C at a heating rate of 5°C / min and kept warm for 3 hours, and then naturally cooled to room temperature to obtain a carbon-based negative electrode material for lithium storage.
[0072] Step 4, assembling the materials obtained in step 3 into a lithium-ion battery and testing the relevant electrochemical properties.
[0073] Example 7
[0074] Compared with Example 6, the mechanical stirring time in step 2 is 5 hours, and the remaining steps are the same.
[0075] Step 1, precursor preparation: select conventional SiO x (x≈1.02) is used as the raw material and further crushed by a jet mill. The parameters are adjusted to ensure that the material D50 is 6-7um, which is recorded as precursor A.
[0076] Step 2, alkaline solution etching: weigh an appropriate amount of NaOH to prepare 0.5 mol / L (abbreviated as M under mol / L) NaOH solution, and then weigh the precursor A obtained in step 1 at a ratio of 1 kg precursor A: 2.5 L NaOH solution for alkaline etching, mechanically stir for 5 hours, wash with deionized water to neutrality, dry at 80°C for 12 hours and set aside, recorded as precursor B.
[0077] Step 3, carbon coating: 1 kg of precursor B was put into a rotary kiln for gas phase carbon coating, acetylene flow rate was 0.8 L / min, the temperature was increased to 865°C at a heating rate of 5°C / min and kept warm for 3 hours, and then naturally cooled to room temperature to obtain a carbon-based negative electrode material for lithium storage.
[0078] Step 4, assembling the materials obtained in step 3 into a lithium-ion battery and testing the relevant electrochemical properties.
[0079] Example 8
[0080] Compared with Example 6, the mechanical stirring time in step 2 is 7 hours, and the remaining steps are the same.
[0081] Step 1, precursor preparation: select conventional SiO x (x≈1.02) is used as the raw material and further crushed by a jet mill. The parameters are adjusted to ensure that the material D50 is 6-7um, which is recorded as precursor A.
[0082] Step 2, alkaline solution etching: weigh an appropriate amount of NaOH to prepare 0.5 mol / L (abbreviated as M under mol / L) NaOH solution, and then weigh the precursor A obtained in step 1 at a ratio of 1 kg precursor A: 2.5 L NaOH solution for alkaline etching, mechanically stir for 7 hours, wash with deionized water to neutrality, dry at 80°C for 12 hours and set aside, recorded as precursor B.
[0083] Step 3, carbon coating: 1 kg of precursor B was put into a rotary kiln for gas phase carbon coating, acetylene flow rate was 0.8 L / min, the temperature was increased to 865°C at a heating rate of 5°C / min and kept warm for 3 hours, and then naturally cooled to room temperature to obtain a carbon-based negative electrode material for lithium storage.
[0084] Step 4, assembling the materials obtained in step 3 into a lithium-ion battery and testing the relevant electrochemical properties.
[0085] Comparative Example 1
[0086] Select conventional SiO x (x≈1.02) is used as the raw material and further crushed by a jet mill. The parameters are adjusted to ensure that the material D50 is 6-7um, which is recorded as precursor A.
[0087] The obtained precursor A was assembled into a lithium-ion battery and the relevant electrochemical properties were tested.
[0088] Comparative Example 2
[0089] Step 1, precursor preparation: select conventional SiO x (x≈1.02) is used as the raw material and further crushed by a jet mill. The parameters are adjusted to ensure that the material D50 is 6-7um, which is recorded as precursor A.
[0090] Step 2, carbon coating: 1 kg of precursor A was put into a rotary kiln for gas phase carbon coating, acetylene flow rate was 0.8 L / min, the temperature was increased to 900°C at a heating rate of 5°C / min and kept at this temperature for 3 hours, and then naturally cooled to room temperature to obtain a carbon-based negative electrode material for lithium storage.
[0091] Step 3, testing the physicochemical parameters of the material obtained in step 2 and assembling it into a lithium-ion battery, and testing the relevant electrochemical properties.
[0092] The test results of the electrochemical properties of the materials are as follows:
[0093] In order to detect the performance of the lithium-ion battery negative electrode material of the silicon oxygen negative electrode material for lithium batteries of the present invention, the above embodiments and comparative examples were tested by a half-cell test method. The negative electrode materials of the above embodiments and comparative examples: SBR: CMC: Super-p = 90: 4: 2: 4 (weight ratio), added with an appropriate amount of deionized water to be mixed into a slurry, coated on a copper foil and dried in a vacuum drying oven for 12 hours to form a negative electrode sheet, the electrolyte was 1M NaPF6 / EC+DEC+PC=1: 1: 1, the Whatman glass fiber filter membrane was used as a diaphragm, the counter electrode was a lithium sheet, and assembled into a 2025 button battery. The constant current charge and discharge experiment was carried out in the LAND battery test system, and the charge and discharge voltage was limited to 0.005-1.5V. The test results are shown in Table 1.
[0094] Table 1 Electrochemical performance data of materials with different magnifications
[0095]
[0096] As can be seen from the above table, by comparing Comparative Example 1 and Comparative Example 2, it can be seen that the carbon coating method can improve the first efficiency of the silicon-oxygen material and the rate performance under 2C.
[0097] Comparing Comparative Example 2 with Example 1, it can be seen that the alkaline solution etching process can further improve the rate performance of the silicon oxide material, while there is basically no change in the primary efficiency.
[0098] Example 1, Example 2, and Example 3 explored the effects of different alkaline etching concentrations on rate performance. As the etching concentration increased, the rate performance first increased and then decreased.
[0099] Example 1, Example 4, and Example 5 explored the effect of coating temperature on the rate performance of silicon-oxygen. As the temperature of small CVD carbon coating increased, the rate performance also increased. However, at the carbon coating temperatures of 900°C and 945°C, the rate performance was not much different.
[0100] Example 6, Example 7, and Example 8 explored the effect of alkaline solution etching time on rate performance. As the etching time increased, the rate performance of silicon oxide also increased.
[0101] Figure 2 This is a SEM image of the high-rate silicon-oxygen negative electrode material prepared in Example 1 of the present invention. It can be seen from the image that after the silicon-oxygen raw material treated with alkali is coated with surface pyrolysis carbon, there are more surface pores, which is beneficial to Li + Transport of ions.
[0102] Figure 3This is the XRD spectrum of the high-rate silicon-oxygen negative electrode material prepared in Example 1 of the present invention. The broad peak located in the range of 20-25° can be attributed to SiO2 with low crystallinity, and the diffraction peaks at 28.44°, 47.3°, and 56.1° correspond to the (111), (220), and (311) crystal planes of crystalline Si.
[0103] Figure 4 This is the charge and discharge curve of the high-rate silicon-oxygen negative electrode material prepared in Example 1 of the present invention. The lithium removal specific capacity of the high-rate silicon-oxygen negative electrode material prepared is 1668.4 mAh / g, and its charging voltage platform is similar to that of silicon-oxygen material.
[0104] Figure 5 This is a rate performance diagram of the high-rate silicon-oxygen negative electrode material prepared in Example 1 of the present invention. The high-rate silicon-oxygen negative electrode material prepared at an etching concentration of 1M, etching for 6 hours, and a carbon coating temperature of 900°C has a 2C discharge performance of 938.0 mAh / g.
[0105] from Figure 3-Figure 5 Judging from the structure and electrochemical performance of the high-rate silicon-oxygen negative electrode material demonstrated, it has successfully prepared a high-rate silicon-oxygen negative electrode material.
[0106] The key innovations of the present invention are:
[0107] The high-rate silicon-oxygen negative electrode material of the present invention has a specific preparation process including crushing of silicon-oxygen raw material precursor, surface etching modification, and carbon coating on the particle surface. Mechanical crushing of block silicon-oxygen particles is selected, and alkaline etching of the crushed silicon-oxygen particles is performed to modify the surface, and then a carbon coating process is performed to obtain a high-rate silicon-oxygen material. The introduction of alkaline etching means can increase the porosity of silicon-oxygen materials, increase the contact between samples and electrolytes, shorten the lithium ion transmission path, increase the Li+ diffusion coefficient, and greatly improve the rate and other properties. The carbon coating means improves its conductivity and can significantly improve the rate performance and cycle performance of the material.
[0108] The above describes the basic principles, main features and advantages of the present invention. The present invention is not limited to the above embodiments. The above embodiments only describe the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which will fall within the scope of the present invention to be protected. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A high-rate silicon-oxygen negative electrode material for lithium batteries, characterized in that: It includes a core and a coating layer, wherein the core material is SiO x , wherein x is 0.8-1.2; the coating layer is a carbon coating layer.
2. A method for preparing a high-rate silicon-oxygen negative electrode material for a lithium battery, characterized in that: The specific steps are as follows: Step 1: Select silicon oxide raw material SiO x , wherein x is 0.8-1.2; using a crushing device to crush the silicon oxygen raw material SiO x crush; Step 2, etching the material crushed in step 1 with an alkaline solution to obtain a surface-modified porous structure material; Step 3, washing the material after alkali etching in step 2 with deionized water until the pH value of the solution is neutral, and drying the washed material in an oven; Step 4, placing the dried material in a coating device for pyrolysis coating, and obtaining a high-rate silicon-oxygen negative electrode material after cooling.
3. The method for preparing a high-rate silicon-oxygen negative electrode material for a lithium battery according to claim 2, characterized in that: The pulverizing equipment in step 1 includes one or more of a toothed pulverizer, a hammer pulverizer, a knife pulverizer, a turbine pulverizer, a pressure mill pulverizer, a milling pulverizer, a jet pulverizer, a ball mill or a sand mill.
4. The method for preparing a high-rate silicon-oxygen negative electrode material for a lithium battery according to claim 2, characterized in that: In step 1, the silicon oxide raw material SiO x After crushing, 50% of the particles have a size of 4-7um.
5. The method for preparing a high-rate silicon-oxygen negative electrode material for a lithium battery according to claim 2, characterized in that: The alkaline solution in step 2 is one or more of NaOH solution and KOH solution.
6. The method for preparing a high-rate silicon-oxygen negative electrode material for a lithium battery according to claim 2, characterized in that: The concentration of the alkaline solution in step 2 is 0.5-1.5 mol / L, and the reaction time is 5-7 h.
7. The method for preparing a high-rate silicon-oxygen negative electrode material for a lithium battery according to claim 2, characterized in that: The water washing in step 3 is to wash the alkali-etched material in step 2 with deionized water until it is neutral. The water washing equipment is one or more of a centrifuge and a positive pressure filtration equipment. The selected oven drying temperature is 70-90°C and the drying time is 12-18h.
8. The method for preparing a high-rate silicon-oxygen negative electrode material for a lithium battery according to claim 2, characterized in that: Step 4 is as follows: add the dried material in step 3 into a rotary kiln, the reaction temperature is 800-950°C, acetylene is introduced at a flow rate of 0.6-1.0L / min for carbon coating, the reaction is carried out for 2-5h, and after cooling, a high-rate silicon-oxygen negative electrode material is obtained.
9. The method for preparing a high-rate silicon-oxygen negative electrode material for a lithium battery according to claim 8, characterized in that: In step 4, the carbon coating method can also be asphalt pyrolysis coating.